A 10,400-molecular-weight membrane protein is coded by region E3 of adenovirus. - Tollefson, A E (1990)
Previous studies with adenovirus mutants have indicated that a 10,400-molecular-weight (10.4K) protein predicted to be coded by an open reading frame in region E3 of adenovirus functions to down regulate the epidermal growth factor receptor (C. R. Carlin, A. E. Tollefson, H. A. Brady, B. L. Hoffman, and W. S. M. Wold, Cell 57:135-144, 1989). We now demonstrate that the 10.4K protein is in fact synthesized in cells infected by group C adenoviruses. This was done by immunoprecipitation of 10.4K from cells infected by a variety of E3 mutants, using antisera against three different synthetic peptides corresponding to the predicted 10.4K sequence. The 10.4K protein was translated primarily from E3 mRNA f, as indicated by cell-free translation of mRNA purified by hybridization from cells infected with an RNA processing mutant that synthesizes predominantly mRNA f. The 10.4K protein was overproduced or underproduced in vivo, respectively, by mutants that overproduce or underproduce E3 mRNA f, also indicating that the 10.4K protein is translated primarily from mRNA f. The 10.4K protein migrated as two bands with apparent molecular weights of 16,000 and 11,000 (10 to 18% gradient gels); both bands contained 10.4K epitopes, as shown by Western blot (immunoblot). Only the 16K band was obtained by cell-free translation, suggesting that the 16K protein is the precursor to the 11K protein. The 10.4K protein is a membrane protein, as shown by cell fractionation experiments and as predicted from its sequence. The predicted 10.4K sequence as well as a putative N-terminal signal sequence and 30-residue transmembrane domain are conserved in adenovirus types 2 and 5 (group C) and in types 3, 7, and 35 (group B).